Diseño e implementación de un sistema de recuperación de energía a partir de purgas laterales, condensados y vapor flash para el calentamiento de agua en procesos industriales. - Quirola Guevara, Daniel Alejandro (2017)
For each component of the heat recovery system there is a theoretical references compilation of applied basic concepts within data surveying before calculations and dimensioning of equipment. With the use of a weighting matrix, an option for the system will be selected by technical criteria. Then, all the system elements will be calculated and dimensioned by Mercerizing and Washing process requirements (pre-heated water receivers), as the same as the condensate return. Once all equipment is completely designed, will begin the construction and implementation. After the calibration and construction of the Project, experimental tests were made to determinate the efficiency. To prevent cloth contamination, chemical tests will run on preheated water recovery mix. Finally, per steam generation, water and oil consumptions reports, indicators of implementation will be calculated to estimate cost saving provided by the project. Since this project has construction materials, recovered tanks and internal/external workforce as direct costs, the sum of this plus engineering and unforeseen events will give the final price.